EXTH-44. INHIBITION OF MerTK ACTIVATES GLIOBLASTOMA-ASSOCIATED MACROPHAGES AND INDUCES TUMOR CELL DEATH IN GLIOMA MICROENVIRONMENT. (11th November 2019) - Su, Yu-Ting; Butler, Madison; Hwang, Lee; Maric, Dragan; Earp, Shelton; Terabe, Masaki; Gilbert, Mark; Wu, Jing
Abstract: BACKGROUND: Glioblastoma-associated macrophages and microglia (GAMs) are the predominant immune cells in the tumor microenvironment. Activation of MerTK, a receptor tyrosine kinase, triggers efferocytosis and polarizes GAMs to an immunosuppressive phenotype, promoting glioma growth. Our previous findings showed that UNC2371, a small-molecule inhibitor of MerTK, induced a less immunosuppressive phenotype of GAMs. Here, we investigate the role of MerTK inhibition on glioblastoma cells in the tumor microenvironment in vitro and in vivo. METHODS: Cytotoxicity of UNC2371 in glioblastoma cells was determined by cell viability and colony formation assays. The protein expression of MerTK, AKT, and Erk were quantified by Western blotting in UNC2371-treated glioblastoma cells. A syngeneic GL261 mouse orthotopic glioblastoma model was used to evaluate the survival benefit of UNC2371 treatment. Fluorescent multiplex immunohistochemistry (IHC) was used to evaluate the expression of CD206, an anti-inflammatory marker on GAMs in murine brain tumor tissues. RESULTS: UNC2371 inhibited GBM cell growth with an EC50 < 100 nM in both human U251 and mouse GL261 glioma cells, but not in GAMs. UNC2371-induced cell death and decreased cell proliferation were demonstrated by colony formation assays. UNC2371 decreased protein expression of phosphorylated MerTK, AKT, and Erk, which are essential for cell survival signaling, in U251 and GL261 cells. Furthermore, UNC2371 treatment prolonged survival in the mouse orthotopic GL261 glioblastoma model, suggesting that UNC2371 induces glioma cell death. A decreased of CD206+ GAMs was found in mice glioma tissues by fluorescent multiplex IHC, consistent with our previous findings in the in vitro cell-based assays. These data suggest that in addition to alleviate immunosuppression in the glioma microenvironment, UNC2371 directly inhibits GBM cell growth in vitro and in vivo. CONCLUSION: Our findings suggest that UNC2371 has a therapeutic benefit via promoting GAM polarization towards proinflammatory status in the glioblastoma microenvironment and unexpectedly, inducing tumor cell death.